The problems of principles of study the graphical programs in training specialists of design profession in higher educational exublishments - Pikushcy, A.I. (Pedagogy of Higher and Secondary Education, 2006)
In article opened the problems concerned with expedition new discipline computer drawing in higher educational establishments in training specialists of design profession.